Fe doping Pd/AC sorbent efficiently improving the Hg0 removal from the coal-derived fuel gas. (15th October 2016) - Han, Lina; He, Xingxing; Yue, Caixia; Hu, Yongfeng; Li, Lina; Chang, Liping; Wang, Hui; Wang, Jiancheng
Graphical abstract: Abstract: Fe doped Pd/AC (where AC is activated carbon) sorbents (1Pd5Fe/AC) were prepared and tested for removal of elemental mercury (Hg 0 ) from coal-derived fuel gas at medium range temperatures (150–250 °C). It is found that the Hg 0 removal efficiency of 1Pd5Fe/AC sorbent was much higher than that of 1Pd/AC sorbent, which has previously been shown to suffer from H2 S poisoning. 1Pd5Fe/AC sorbent can maintain its Hg 0 removal efficiency above 92% for 6 h at 200 °C. The fresh and used sorbents were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and X-ray absorption spectroscopy (XAS). The results indicated that the Hg 0 removal active components of the 1Pd5Fe/AC sorbent were elemental Pd and Fe2 O3 . The elemental Pd could react with mercury vapor to form Pd-Hg amalgam. Fe2 O3 could react with H2 S to produce elemental sulfur which can combine with Hg 0 to form HgS. It is worth noting that PdO existed in both 1Pd5Fe/AC and 1Pd/AC sorbents and could react with H2 S to form PdS, which results in the deactivation of sorbents. But Fe2 O3 on the surface of 1Pd5Fe/AC sorbent can compete with PdO to react with H2 S to produce elemental sulfur, thus inhibiting the deactivation of 1Pd5Fe/AC sorbent. In addition, H2 and CO were found to promote the Hg 0 removal efficiency. The used 1Pd5Fe/AC sorbent could successfully be regenerated and reused for Hg 0 removal.